Floating-zone growth of Na(0.8-y)A(y)CoO(2) (A=Ca, Sr) single crystals - Prabhakaran, D; Boothroyd, A (2011)
Single crystals of Na0.8-yAyCoO2 (A=Ca, Sr; y=0.10.3) have been grown using the optical floating-zone method for the first time. We have determined the optimum growth conditions to grow the highest quality single crystals. Columnar growth behavior has been observed for the higher doped samples. The magnetic and structural ordering temperatures of the doped samples were found to vary considerably. Crown Copyright © 2010 Published by Elsevier B.V. All rights reserved.